Purification of papain from Carica papaya latex: Aqueous two-phase extraction versus two-step salt precipitation - Nitsawang S. (2014)
Purification of papain from wet Carica papaya latex by extraction in aqueous two-phase system was studied and compared with the traditional procedure involving a two-step salt precipitation. The papain obtained by the latter method was usually contaminated with other proteins, and its purity was dependent on the initial protein concentration in the material used for processing. Highly pure papain was obtained in a much shorter processing time directly from unclarified latex with the use of an aqueous two-phase system consisting of 8% (w/w) polyethylene glycol and 15% (w/w) ammonium sulfate. © 2006 Elsevier Inc. All rights reserved.